Direct selling strategies and customers loyalty in the Nigerian deposit money banks - Okoro Uzochukwu, Odeleye Olayinka Tope, Tejere Efe, Onyeike Kelechi Thankgod (International journal of economic perspectives, 2021)
Direct Selling has become a veritable part of business success story particularly in the deposit money bank of Nigeria. The main objective of this study is to examine the effect of direct selling strategies on customer’s loyalty in the Nigerian deposit money banks. Primary data was used for the study. The data were collected through a structured questionnaire. The study adoptedthe cross-sectional survey research design method. The population of the study was 812 employees from selected deposit money banks (Zenith Bank, GTBank, UBA, First Bank, and Fidelity Bank) in Delta State. A total number of 260 respondents were selected as the sample size. To validate the instrument, face and content validity were adopted. Descriptive statistics were used to analyze the responses from the respondents. Multiple regression analysis was applied to analyze the effect of the variables of directselling strategies on customer’s loyalty. Findings show that face-to-face communication (β = 0.185. p<0.01), sales team cohesion (β=0.196, p<0.01), sales technology (β=0.328, p<0.01) and adaptive selling style (β= 0.293, p<0.01) exhibited significant positive effect on customers loyalty.